Extraordinary enhancement of porphyrin photocurrent utilizing plasmonic silver arrays. Issue 34 (15th July 2016) - Sugawa, Kosuke; Uchida, Koji; Takeshima, Naoto; Jin, Shota; Tsunenari, Natsumi; Takeda, Hideyuki; Kida, Yuki; Akiyama, Tsuyoshi; Otsuki, Joe; Takase, Kouichi; Yamada, Sunao
Abstract : We demonstrate up to ∼630-fold enhancement of the photocurrent from a porphyrin monolayer on a plasmonic Ag-array electrode showing plasmon absorption in the Q-band region relative to that on a planar Ag electrode Abstract : We demonstrate up to ∼630-fold enhancement of the photocurrent from a porphyrin monolayer on a plasmonic Ag-array electrode showing plasmon absorption in the Q-band region relative to that on a planar Ag electrode. The photocurrent obtained by the Q-band excitation in the plasmonic electrodes even exceeded that obtained by the Soret-band excitation in a normal, nonplasmonic electrode.